Optimization of Hemoglobin Chitosan Glycosylation Conditions and Structural Characteristics and Functions of Glycosylated Hemoglobin after an In vitro Digestion. Issue 7 (9th August 2021) - Zhan, Junqi; Li, Gaoshang; Tan, Beibei
ABSTRACT: The relation of glycosylation and function in Tegillarca Granosa hemoglobin was explored in this study. The manuscript firstly discusses the conditions of glycosylation between chitosan and hemoglobin, as well as the properties and functions of glycosylated hemoglobin. The results showed that optimal conditions for glycosylation of chitosan and hemoglobin were mass fraction ratio of hemoglobin and chitosan of 4:1, pH 5.5, reaction time of 15 min, reaction temperature of 55°C. After glycosylation, surface hydrophobicity, antioxidant, iron bioavailability of hemoglobin increased by 179.78%, 11.06%, 22.96% respectively; while water holding capacity, protein digestibility decreased by 24.80%, 30.49% respectively. Moreover, glycosylation increased structural stability of hemoglobin due to FT/IR absorption peaks without significant changes before and after In vitro digestion, meaning that glycosylated hemoglobin was more resistant to degradation. Therefore, glycosylation could make hemoglobin structure stable and enhance its antioxidation and iron supplement, which provides theoretical basis for application of glycosylation in food.